Technical Note: A comparison of central and peripheral intraocular pressure using rebound tonometry - Queirós, A. (2007)
Purpose: To compare central and peripheral intraocular pressure (IOP) readings obtained with rebound tonometry.Methods: Intraocular pressure was measured on the right eye of 153 patients (65 males, 88 females), aged from 21 to 85 years (mean +/- S.D., 55.5 +/- 15.2 years) with the ICare rebound tonometer at centre, and 2 mm from the limbus (in the nasal and temporal regions along the 0-180O corneal meridian).Results: Intraocular pressure values obtained with the ICare were 14.9 +/- 2.8; 14.1 +/- 2.5 and 14.5 +/- 2.7 mmHg at centre, nasal and temporal corneal locations, respectively. On average, nasal and temporal IOP readings were 0.75 and 0.37 mmHg lower than the central reading (p < 0.05 and p > 0.05, respectively). A highly significant correlation was found between central and peripheral measurements in nasal (r(2) = 0.905; p < 0.001) and temporal (r(2) = 0.879; p < 0.001) regions along the horizontal meridian. Almost 80% of patients presented nasal IOP values within +/- 1 mmHg of the central value.Conclusions: Intraocular pressure values measured with the ICare (R) rebound tonometer on the nasal corneal region is slightly lower on average and highly correlated with IOP values recorded at corneal centre. Both nasal and temporal readings are in good agreement with central IOP, and could be used to obtain a reliable estimate of rebound IOP in corneas where central readings cannot be taken.